Madison and the Smart Mob: The Promise and Limitations of the Internet for Democracy - Faris, Robert; Etling, Bruce (Tufts Archival Research Center, 2005)
Volume 32, Issue 2. Summer "Color revolutions" in countries as disparate as Burma and the Ukraine demonstrate the potential of the Internet and text messaging for disseminating democratic ideals. These new technologies have no doubt revolutionized peer-to-peer relationships, but they remain limited in improving processes among government institutions.